1999
DOI: 10.1111/j.1469-7793.1999.163af.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms by which adenosine induces vasodilatation in rat skeletal muscle: significance for systemic hypoxia

Abstract: In previous studies we have provided evidence, by using adenosine receptor antagonists, that a major part of the vasodilatation induced in skeletal muscle of the rat during systemic hypoxia is mediated by adenosine (Neylon & Marshall, 1991). From the effects of glibenclamide, which inhibits ATP-sensitive K¤ (KATP) channels, we argued that a part of the hypoxia-induced muscle vasodilatation, particularly the early part, is dependent on the opening of KATP channels (Marshall et al. 1993). On the other hand, sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
104
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(121 citation statements)
references
References 29 publications
16
104
1
Order By: Relevance
“…The actions of Ado have been linked to K ATP channel activation in skeletal muscle (8,10) as well as in other tissues (18,22). However, we were unable to attenuate Ado-induced dilations with the concentration of glibenclamide that significantly attenuated both a pinacidil-induced local dilation (Fig.…”
Section: Role Of Ado Receptorsmentioning
confidence: 63%
See 1 more Smart Citation
“…The actions of Ado have been linked to K ATP channel activation in skeletal muscle (8,10) as well as in other tissues (18,22). However, we were unable to attenuate Ado-induced dilations with the concentration of glibenclamide that significantly attenuated both a pinacidil-induced local dilation (Fig.…”
Section: Role Of Ado Receptorsmentioning
confidence: 63%
“…Because both Ado and NO have been identified as playing a role in active hyperemia in hamster cremaster muscle, we explored their contributions to these dilations by using an Ado receptor antagonist [xanthine amine congener (XAC), an A 1 , A 2A , and A 2B membrane receptor antagonist] and a NO synthase inhibitor [N -nitro-L-arginine (L-NNA)]. The actions of Ado receptor activation (8,10,18,22) and NO dilator capacity (27,42) have been linked to ATP-sensitive potassium (K ATP ) channel function. At the microvascular level, K ATP channels are functional in arterioles at rest (18), and both Ado and K ATP channels have been identified as important in arteriolar dilations during muscle contraction (32,36).…”
mentioning
confidence: 99%
“…Previous studies on the influence of adenosine on the splanchnic circulation, including the pancreas, have unequivocally demonstrated that the vasodilating effects are mediated by A 2 receptors (18,24). However, a vasodilator response mediated by A 1 receptors exists in other vascular beds, e.g., the diaphragm (14) and other skeletal muscle (8,9,38).…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that both A 2a and V 1 receptors may act via stimulation of NOS because the activation of both of these receptors increases intracellular calcium (9,17,27,29). NO released from NTS neurons/synaptic terminals after activation of A 2a and V 1 receptors may activate pre-or postsynaptically those glutamatergic neurons that send their axons to the CVLM and finally inhibit RSNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also demonstrated that central blockade of vasopressin V 1 receptors and nitric oxide (NO) synthase (NOS) attenuates posthemorrhagic hypotension (10,25). In addition, activation of both adenosine A 2a and vasopressin V 1 receptors may activate NOS because they both increase intracellular calcium levels (9,17,27,29). Therefore, adenosine, vasopressin, and NO may interact in creating the pattern of autonomic responses observed during hypotensive hemorrhage.…”
mentioning
confidence: 99%